2003
DOI: 10.1523/jneurosci.23-07-02591.2003
|View full text |Cite
|
Sign up to set email alerts
|

GABA Is Dispensable for the Formation of Junctional GABA Receptor Clusters inCaenorhabditis elegans

Abstract: At GABAergic synapses, GABA receptors form high-density clusters opposite GABA release sites. Whether GABA release per se plays a role in the formation of GABA receptor clusters remains uncertain. To address this question in vivo, we characterized GABA receptor clustering in the nematode Caenorhabditis elegans. In C. elegans, body wall muscles receive excitatory inputs from cholinergic motor neurons and inhibitory inputs from GABAergic neurons. Using immunohistochemistry and green fluorescent protein-tagged pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 62 publications
10
56
1
2
Order By: Relevance
“…The results described by Jiang et al (2005) strongly imply that the recycling function is more critical for GABAergic neurotransmission in C. elegans because snf-11 RNAi results in a GABAergic "loss-of-function" phenotype. Alternatively, Jiang et al (2005) suggest that GABA receptors have been down-regulated; however, other studies fail to support this view (Gally and Bessereau, 2003). In contrast, our results clearly indicate that the GABA transporter in C. elegans functions chiefly in the clearance of GABA.…”
Section: Discrepancies With a Previous Study On Snf-11contrasting
confidence: 77%
“…The results described by Jiang et al (2005) strongly imply that the recycling function is more critical for GABAergic neurotransmission in C. elegans because snf-11 RNAi results in a GABAergic "loss-of-function" phenotype. Alternatively, Jiang et al (2005) suggest that GABA receptors have been down-regulated; however, other studies fail to support this view (Gally and Bessereau, 2003). In contrast, our results clearly indicate that the GABA transporter in C. elegans functions chiefly in the clearance of GABA.…”
Section: Discrepancies With a Previous Study On Snf-11contrasting
confidence: 77%
“…Altogether, these observations confirm that neurotransmitter-mediated activity is not essential for synapse formation (91)(92)(93)(94) and indicate that differential mechanisms ensure long-term stability of synapses in various cell compartments. While the normal morphology and content of presynaptic vesicles of basket cell terminals suggest that these terminals remain competent for GABA synthesis and release, activation of postsynaptic GABA A receptors is not required for maintenance of this synapse.…”
Section: Requirement Of Gaba a Receptors For Longterm Maintenance Of supporting
confidence: 60%
“…At the light level, fluorescently tagged synaptic vesicles appeared to cluster normally in GABA neurons [15]. The postsynaptic inhibitory GABA receptor also appeared to have a normal distribution in unc-25 mutants [18]. A reconstruction of the ventral nerve cord from serial electron micrographs demonstrated that the synaptic structure and connectivity were correct [15].…”
Section: Unc-25: Is Gaba Required For Development?mentioning
confidence: 95%